2018
DOI: 10.1111/jmi.12755
|View full text |Cite
|
Sign up to set email alerts
|

Superior robustness of ExEm‐spFRET to IIem‐spFRET method in live‐cell FRET measurement

Abstract: Summary We recently developed two quantitative fluorescence resonance energy transfer (FRET) measurement methods based on spectral unmixing of emission spectra (IIem‐spFRET) and excitation–emission spectra (ExEm‐spFRET), respectively. We here evaluated robustness of the two methods by implementing them on a self‐assembled quantitative FRET measurement system using the cells expressing different constructs. For the cells with larger signal‐to‐noise (S/N) ratio (>9), the two methods obtained consistent FRET effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Fluorescence resonance energy transfer (FRET) analysis was performed on a user‐built microscope–spectrometer (MSM) platform that consisted of a widefield fluorescence microscope (Axio Observer, Carl Zeiss, Oberkochen, Germany) with a ×40/1.3 NA oil objective and a miniature fibre optic spectrometer (QE65 Pro, Ocean Optics, FL, USA). FRET efficiency was quantified according to the IIem‐spFRET measurement method (Zhang et al ., 2016; Lin et al ., 2018). At least 15 individual protoplasts were used for FRET efficiency quantification and statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence resonance energy transfer (FRET) analysis was performed on a user‐built microscope–spectrometer (MSM) platform that consisted of a widefield fluorescence microscope (Axio Observer, Carl Zeiss, Oberkochen, Germany) with a ×40/1.3 NA oil objective and a miniature fibre optic spectrometer (QE65 Pro, Ocean Optics, FL, USA). FRET efficiency was quantified according to the IIem‐spFRET measurement method (Zhang et al ., 2016; Lin et al ., 2018). At least 15 individual protoplasts were used for FRET efficiency quantification and statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…4c). When performing FRET analysis based on the IIem-spFRET method (Zhang et al, 2016;Lin et al, 2018), both SNF7A and SNF7B showed interactions with FYVE4 on these puncta (Fig. 4d).…”
Section: Fyve4 Associates With the Escrt-iii Complexmentioning
confidence: 99%
“…All raw scans used for spectral FRET are available in S2 Fig. Once the contributing weight of donor and acceptor was determined, FRET efficiency was estimated using the following equation[27]: where E is the FRET efficiency, W A and W D are the component weights of the donor only and acceptor only emissions calculated through linear unmixing, and QY A and QY D is the quantum yield of the acceptor and donor respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For each of the acceptors, custom acceptor only scans were created based on experimentally collected data and their reported purified spectrum (as discussed in S1 Fig). All raw scans used for spectral FRET are available in S1 Fig. Once the contributing weight of donor and acceptor was determined, FRET efficiency was estimated using the following equation [27]:…”
Section: Spectral Fretmentioning
confidence: 99%